Humanisme Teosentris: Telaah Sosiologi Pengetahuan Pemikiran Kuntowijoyo - Isfaroh Isfaroh (LP2M UIN Sunan Kalijaga, 2020)
This study explores the ideas and thoughts of Kuntowijoyo, especially as they relate to the social construction of his thought on humanism, which is developed through three phases; externalised reality, objectified reality, and internalised reality. The data was collected through library studies, involving reviews of primary and secondary sources. The collected data was analysed using deductive and inductive approach, verstehen method to explore Kuntowijoyo’s ideas of humanism, as well as sociological approach to examine the social construction of his thought of humanism, which is considered theocentric. The finding shows that the thought of Kuntowijoyo oh humanism is socially constructed through dialectical triad, namely: externalised reality, objectified reality, and internalised reality. Such dialectical triad work simultaneously in the development of Kuntowijoyo thought on humanism.[Kaijan ini mencoba menelusuri gagasan dan pemikiran Kuntowijoyo, khususnya berkenaan dengan konstruksi sosial yang membentuk pemikirannya tentang humanisme, yang berkembang melalui tiga fase; realitas eksternal, realitas objektif, dan realitas internal. Data penelitian ini bersumber dati kajian pustaka, termasuk telaah pada sumber primer dan sumber sekunder. Data yang telah dikumpulkan kemudian dianalisa menggunakan pendekatan deduktif dan induktif, metode verstehen untuk menelusuri konstruksi sosial dari pemikiran Kuntowijoyo mengenai humanisme, yang dianggap sebagai teosentris. Temuan dari penelitian ini menunjukkan bahwa pemikiran Kuntowijoyo mengenai humanisme terbentuk secara sosial melalui dialektika triadik, yaitu: realitas eksternal, realitas objektif, dan realitas internal. Dialektika triadik itu secara simultan dapat menggambarkan proses perkembangan pemikiran Kuntowijoyo tentang humanisme.]